Improving the tolerance of vicia fabaagainst environmental salinity resulted from the irrigation with sea water by using k2 so4 and (nh4)2so4 as chemical osmoregulators. (2012)
Vicia faba L. was cultivated with irrigation with 5, 10, 15 and 20% (v:v) sea water. The plants were divided to three groups. The first was irrigated without treatments while the second was treated with 5 mM KNO3 and the third was treated with 5mM (NH4)2 SO4. The plants were left to grow until flowering stage. The famous solutes Na+, K+, Ca2+, Mg2+, Cl-, PO43-, SO42-, soluble carbohydrates, amino acids and soluble proteins were estimated to investigate the role of potassium nitrate and ammonium sulphates as osmoregulators. The results indicated that the non-treated group increased the soluble carbohydrates in the roots to avoid the influx of sodium. The treatment with KNO3 decreased the sodicity (SAR) in the shoots. The availability of nitrogen as nitrate or ammonium ions enhances the accumulation of soluble carbohydrates in shoots. KNO3 treatment decreased SAR strongly while (NH4)2 SO4 treatment the SK:Na value in the shoots at higher salinity. The plants of all groups were depended on Ca2+ as compatible solute more than Na+ and K+.